Neutrino emissivity in the color superconducting quark‐hadron‐mixed phase. Issue 1 (28th March 2019) - Freeman, A.; Farrell, D.; Weber, F.; Spinella, W. M.; Orsaria, M. G.; Contrera, G. A.
Abstract : The tremendously high pressures that exist in the cores of neutron stars may break up neutrons, protons plus other hadronic particles into their quark constituents. This transition from hadronic matter to quark matter could lead to an extended quark‐hadron‐mixed phase region in the cores of neutron stars that would segregate phases by net charge to minimize the total energy of the phase, leading to the formation of a crystalline quark‐hadron Coulomb lattice. The neutrino emissivity due to the elastic scattering of electrons off the lattice was previously studied where it was assumed that the quark lattice sites are made of ordinary (i.e., nonsuperconducting) quark structures (blobs, rods, and slabs). In the present study, we extend these calculations to the elastic scattering of electrons off quark blobs that are in the color superconducting color‐flavor‐locked (CFL) phase. As this phase reduces the electric charge carried by quark blobs, the electric charge density of CFL blobs is smaller than that of non‐CFL blobs. The neutrino emission rates, however, change only minimally.